2018
DOI: 10.1039/c8qo00413g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-aminobenzaldehydes by rhodium(iii)-catalyzed C–H amidation of aldehydes with dioxazolones

Abstract: Various aldehydes were directly amidated with dioxazolones to afford 2-aminobenzaldehydes through rhodium(iii)-catalyzed CHO-directed C–H activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Based on literature reports and our preliminary control experiments, we proposed a plausible reaction mechanism (Scheme ). Initially, the cationic Co III complex A can undergo initial ligand exchange with in situ generated aldimines from benzaldehyde 1 a and aniline to give complex B .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature reports and our preliminary control experiments, we proposed a plausible reaction mechanism (Scheme ). Initially, the cationic Co III complex A can undergo initial ligand exchange with in situ generated aldimines from benzaldehyde 1 a and aniline to give complex B .…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Cp*Co(III) catalysts have been utilized for C−H bond amidation by Chang and later by Jiao, Ackermann, Li, Matsunaga, Sundararaju and others . Interestingly, Dong and co‐workers reported Cp*Rh(III)‐catalyzed amidation via in situ generation of a traceless directing group through combination of aldehydes and dioxazolones. Additionally, Zhang reported an elegant H 2 O promoted amidation of benzaldehydes under Cp*Rh catalysis.…”
Section: Methodsmentioning
confidence: 99%
“…The computational studies indicated the formation of the active rhodium species 27 by the interaction between rhodium catalyst precursor with water in the presence of dioxazolones. The active rhodium species would then undergo the ortho-metalation assisted by the aldehyde functionality through a concerted-metalation-deprotonation (CMD) process [24] to form a rhodacycle intermediate 23 Meanwhile, Dong and co-workers [25] presented a method for rhodium-catalyzed ortho-CÀ H amidation of benzaldehydes with dioxazolones under air. The authors suggested that the reaction likely proceeded through aldehyde-directed CÀ H activation.…”
Section: Cà N and Cà O Bonds Formationmentioning
confidence: 99%
“…reported that an external amine source (aniline) is required to achieve Rh(III)‐catalyzed ortho C−H amidation of benzaldehydes 10 (Scheme 18a). However, an independent report by Dong group [23b] revealed that, when an aminating/amidating agent is able to form imine in situ from aldehyde, the external transient ligand is not required (Scheme 18b). Thus a dioxazolone 7 in situ forms a transient imine functionality to promote the synthesis of 2‐aminobenzaldehyde derivative 11 .…”
Section: Cp*rh(iii)‐catalyzed Directed Ortho Sp2(c)−h Amidation or Ammentioning
confidence: 99%